Maximum voltage sag compensation using direct converter by modulating the carrier signal - S. Abdul Rahman; Gebrie Teshome (International Journal of Electrical and Computer Engineering (IJECE), 2020)
The aim of this paper is to achieve maximum voltage sag compensation of 52% using direct converter based DVR. The DVR topology has only two switches. The DVR is designed to compensate the voltage sag in a phase by taking power from the same phase. A direct converter is connected between the series transformer and the line in which sag compensation is to be achieved. If the actual amplitude of the error signal is used and the amplitude of carrier signal is kept at 1 unit, it is possible to achieve only 22% of sag compensation. If the amplitude of the carrier signal is modulated according to the percentage of existing sag, 52% of the sag is compensated through ordinary PWM technique with the THD less than 5%. Matlab Simulation results are presented for the validating the analysis.